2013
DOI: 10.1021/es4015844
|View full text |Cite
|
Sign up to set email alerts
|

Release of Silver from Nanotechnology-Based Consumer Products for Children

Abstract: We assessed the potential for children's exposure to bioavailable silver during the realistic use of selected nanotechnology-based consumer products (plush toy, fabric products, breast milk storage bags, sippy cups, cleaning products, humidifiers, and humidifier accessory). We measured the release of ionic and particulate silver from products into water, orange juice, milk formula, synthetic saliva, sweat, and urine (1:50 product to liquid mass ratio); into air; and onto dermal wipes. Of the liquid media, swea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(144 citation statements)
references
References 41 publications
(65 reference statements)
5
138
0
1
Order By: Relevance
“…MES (2-(Nmorpholino)ethanesulfonic acid) buffer (10 mM, pH 5.6) and borate buffers (1 mM, pH 7.4 and 8.5) were used to control the pH, and diluted HNO 3 and NaOH were used to adjust the pH values. Moreover, the effect of temperature (6, At each time interval during the experiment, 5 mL of the sample was taken from the bottle and mixed with 2.5 mL saturated EDTA solution for 10 min.…”
Section: Silver Transformation Experimentsmentioning
confidence: 99%
“…MES (2-(Nmorpholino)ethanesulfonic acid) buffer (10 mM, pH 5.6) and borate buffers (1 mM, pH 7.4 and 8.5) were used to control the pH, and diluted HNO 3 and NaOH were used to adjust the pH values. Moreover, the effect of temperature (6, At each time interval during the experiment, 5 mL of the sample was taken from the bottle and mixed with 2.5 mL saturated EDTA solution for 10 min.…”
Section: Silver Transformation Experimentsmentioning
confidence: 99%
“…20 The authors suggested that the discrepancy in silver release between the products could be attributed to the method used to treat the fibers of the product with silver. Our simulated use scenario (Fig.…”
Section: 21mentioning
confidence: 99%
“…1,[11][12][13][14][15][16][17][18][19] More recently, investigators have begun to focus on release of silver into biological fluids and the exposure potential from contact with textile consumer products. 20,21 These studies have reported that silver in textiles was released primarily in ionic form into artificial sweat at varying levels depending on the product tested. However, little is known about the factors that influence silver exposure from the use of textile consumer products.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a study on the release of ionic and particulate silver from nanotechnology-based consumer products for children has been published (Quadros et al, 2013). During realistic use of a number of consumer products (plush toy, fabric products, breast milk storage bags, cleaning products, humidifiers and accessories), measurements were taken of the release of Ag into water, orange juice, milk formula, synthetic saliva, sweat, urine, into air and onto dermal wipes.…”
Section: Products For Childrenmentioning
confidence: 99%
“…In the same report, Quadros et al (2013) tried to put the leakage of silver into perspective. They compared the amount of silver released from products to the results of a study rats by Kim et al (2007), on the toxicity of nanosilver in rats after oral administration.…”
Section: Products For Childrenmentioning
confidence: 99%